Endoplasmic reticulum aminopeptidase 1 (ERAP1) plays a critical role in determining the length and sequence of peptides bound and presented by HLA-B27 - Chen, L; Fischer, R; Peng, Y; Reeves, E; McHugh, K; Ternette, N; Hanke, T; Dong, T; Elliott, T; Shastri, N; Kollnberger, S; James, E; et al. (Wiley-Blackwell, 2013)
Objective. HLA-B27 and ERAP1 are the two strongest predisposing genetic factors to Ankylosing Spondylitis (AS). A key aminopeptidase in MHC class I presentation, ERAP1 potentially contributes to AS pathogenesis through altering HLA-B27 peptide presentation. We studied the effects of ERAP1 on the HLA-B27 peptide repertoire and peptide presentation to Cytotoxic T lymphocytes (CTLs). Methods. ERAP1-silenced and -competent HeLa.B27/C1R.B27 cells were isotope labeled, mixed, lysed and then immuno-precipitated using W6/32 or ME1. Peptides bound to HLA-B27 were eluted and analyzed by tandem Mass Spectrometry. Selected peptides were synthesized and tested for HLA-B27 binding ability. The effect of ERAP1 silencing/mutation on presentation of an immunodominant viral HLA-B27 epitope, KK10, to CTL was also studied. Results. In both HeLa.B27 and C1R.B27 cells, the proportion of 9mer HLA-B27-bound peptides was decreased by ERAP1 silencing, whereas the percentage of longer peptides (11-13mers) increased. Surprisingly, following ERAP1 silencing, C-terminally extended peptides were readily identified. These were better able to bind to HLA-B27 than N-terminally extended peptides lacking a P2 Arginine. In both HeLa.B27 and mouse fibroblasts expressing HLA-B27, the absence of ERAP1 reduced recognition by HLA-B27-restricted KK10-specific CTLs following recombinant vaccinia viral infection or transfection with minigenes expressing KK10 precursors. Lastly, an AS protective variant, K528R-ERAP1, reduced KK10 CTL recognition following extended-KK10 minigene transfection compared to WT-ERAP1. Conclusion. Our study shows that ERAP1 directly alters peptide binding and presentation by HLA-B27, supporting a pathogenic mechanism in AS. ERAP1 inhibition could potentially be used for treatment of AS and other ERAP1-associated diseases. © 2013 American College of Rheumatology.